Effect of Soaking Treatments in Acid and Salt Solutions on Physicochemical, Structural, Thermal and Rheological Properties of Porang (Amorphophallus muelleri Blume) Flour - Lia Ratnawati; Novita Indrianti; Nok Afifah; Riyanti Ekafitri; Enny Sholichah; Dewi Desnilasari; Woro Setiaboma; Dita Kristanti; Achmat Sarifudin (Food Technology and Biotechnology)
Research background. Porang (Amorphophallus muelleri Blume) contains a high amount of starch, glucomannan and Ca-oxalate. Soaking porang tuber in acid (citric acid) and salt (sodium chloride) solutions affects the Ca-oxalate content, functional, rheological and thermal properties of porang flour. The aim of this study is to thoroughly investigate the effect of soaking treatments in acid and salt solutions at different temperatures on the physicochemical, rheological and thermal properties, functional groups, molecular mass and morphology of porang flour. Experimental approach. Soaking treatments in acid and salt solutions at different temperatures affect the properties of porang flour. This research investigated the effect of soaking porang slices in citric acid (5 %) and sodium chloride (8 %) solutions at different soaking temperatures (25, 55 and 85 °C for 1 h) on the properties of the resulting porang flour. Results and conclusions. The results of this study showed that all treatments successfully reduced the Ca-oxalate mass fraction in porang flour. The acid treatments reduced the glucomannan content more than the salt treatments. Soaking in acid solutions also decreased viscosity, molecular mass and thermal stability of porang flour. When the soaking temperature was increased, the Ca-oxalate mass fraction, molecular mass, viscosity and thermal stability of the porang flour decreased. The acid and salt treatments did not change the FTIR patterns. The morphological analysis showed that the acid and salt treatments resulted in particles with rough surface and short crystal needles of Ca-oxalate. Soaking the porang slices in salt solution at a temperature of 55 °C was the most effective treatment to reduce the Ca-oxalate content of porang flour while retaining its other quality parameters. Novelty and scientific contribution. The results of this study provided a comprehensive understanding of the effect of soaking porang slices in acid and salt solutions on the properties of the obtained porang flour. They can be used as scientific evidence on how to treat the porang slices to obtain the best quality of porang flour.